PERENNIAL SOWTHISTLE (SONCHUS ARVENSIS) INTERFERENCE IN SOYBEAN (GLYCINE MAX) DRY EDIBLE BEAN (PHASEOLUS VULGARIS). - ZOLLINGER, RICHARD K.
Field experiments were conducted in 1987 and 1988 to examine interference from a natural population of perennial sowthistle on soybean and dry edible bean. In 1987, an average of 78 and 90 perennial sowthistle shoots per m2 in 71-cm (wide) crop row spacing reduced soybean and dry edible bean yield by 49% and 36%, respectively. In 1988, a year of les s precipitation, an average density of 96 and 88 shoots per m2 reduced soybean and dry bean yield by 87% and 83%, respectively. One cultivations 5 wk after planting increased crop yield and decreased perennial sowthistle density compared with no cultivation. Perennial sowthistle reduced seed weight, germi- nation percentage, and seedling growth rate of seed produced by both crops. In the presence of perennial sowthistle, one cultivation resulted in improved seed quality compared with no cultivation. Nomenclature: Perennial sowthistle, Sonchus arvensis L. #3 SONAR; dry edible bean, Phaseolus vulgaris L. var. navy `C-20`; soybean, Glycine max L.